Mekanisme Pengelolaan Dan Pendistribusian Zakat, Infak Dan Sedekah Di Daarut Tauhid Peduli Garut - Syaripudin, Enceng Iip; Nuraeni, Imel (Jurnal Hukum Ekonomi Syariah, 2022)
Economic issues are crucial for individuals, communities, and nations. Zakat, infaq, and sedekah (ZIS) have significant potential for empowering communities. Hence, there is a need for an analysis of the mechanisms of managing and distributing zakat, infaq, and sedekah, as concerns arise regarding discrepancies in both management and distribution of ZIS at DT Peduli Garut according to Islamic sharia principles. The research problem formulation is as follows: What is the mechanism of managing zakat, infaq, and sedekah at Daarut Tauhid Peduli Garut? What is the mechanism of distributing zakat, infaq, and sedekah at Daarut Tauhid Peduli Garut? And what is the analysis of the mechanisms of managing and distributing zakat, infaq, and sedekah at Daarut Tauhid Peduli Garut? The objective of this research is to understand the mechanisms of managing and distributing zakat, infaq, and sedekah at Daarut Tauhid Peduli Garut. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results of the research on the mechanisms of managing and distributing zakat, infaq, and sedekah at Daarut Tauhid Peduli Garut are considered appropriate because at Daarut Tauhid, the management process adheres to Islamic sharia principles. This includes management in accordance with the Qur'an, Hadith, jurisprudence of zakat, infaq, and sedekah (ZIS), and fatwas issued by the Sharia Council of Daarut Tauhid. Keywords: Management, Distribution, ZIS.